Wall Works - Wall Installations in Editions 1992-93. - Edition Schellmann, Köln; Edition Schellmann, New York (Köln : Edition Schellmann, 1993)
Artschwager, Richard ; Arakawa, Shusaku ; Buren, Daniel ; Flavin, Dan ; Förg, Günther ; Gilbert & George ; Grünfeld, Thomas ; Halley, Peter ; Hirst, Damien ; Judd, Donald ; Kosuth, Joseph ; Knoebel, Imi ; Kounellis, Jannis ; LeWitt, Sol ; Merz, Gerhard ; Paolini, Giulio ; Rückriem, Ulrich ; Ruthenbeck, Reiner ; Sherman, Cindy ; Steinbach, Haim
boek